2021
DOI: 10.1111/ijn.12932
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a cognitive rehabilitation programme on cognitive function, self‐management and quality of life in patients with chronic obstructive pulmonary disease

Abstract: Aim: The study purpose was to investigate effects of a cognitive rehabilitation programme on cognitive function, self-management and quality of life in patients with chronic obstructive pulmonary disease.Background: Cognitive impairment is frequently observed in chronic obstructive pulmonary disease patients, and it interferes with many aspects of self-management, which is fundamental to disease management and quality of life.Design: The design is quasi-experimental. Methods: Data collection was performed betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The beneficial effects of cognitive interventions for healthy individuals and those with various cognitive impairments have been discussed in several studies [ 14 - 17 ]. However, its effects on people with CRDs have never been systematically documented [ 4 , 16 - 18 ]. To our knowledge, this is the first systematic review focusing on the effects of cognitive intervention in individuals with CRDs.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of cognitive interventions for healthy individuals and those with various cognitive impairments have been discussed in several studies [ 14 - 17 ]. However, its effects on people with CRDs have never been systematically documented [ 4 , 16 - 18 ]. To our knowledge, this is the first systematic review focusing on the effects of cognitive intervention in individuals with CRDs.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, concerning the comparison between the cognitive, psychological, quality of life, and functional data at admission and discharge, a significant improvement can be observed in all the investigated areas in CHF and COPD patients. The data concerning the benefits of cardiac and pulmonary rehabilitation has been extensively reported in literature in both CHF and COPD patients [41,[57][58][59][60][61][62][63][64][65]. As to CHF, literature shows that cardiac rehabilitation induced significant improvements in physical and psychological parameters in a sample of patients ranging from less than 65 years to 80 years or over [59].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning COPD, a recent systematic review, performed on nineteen randomized controlled trials that compared pulmonary rehabilitation groups with usual care groups, showed statistically significant improvements in patient's quality of life [60]. A recent study showed significant improvements in COPD patients' cognitive functions after a rehabilitation program focused on attention, memory, language, visuospatial perception, executive functions, and problem-solving [65]. Moreover, the results of a prospective study in which COPD older patients performed an 8-week pulmonary rehabilitation program, showed a sustained improvement in anxiety and quality of life 2 years after the intervention [64].…”
Section: Discussionmentioning
confidence: 99%
“…15 Such discoveries, however, do not offer assistance to those with T2DM for managing cognitive dysfunction and DM. Cognitive rehabilitation has improved self-management in persons with other chronic conditions such as heart failure and "chemo brain," 16 but few studies have used cognitive rehabilitation to improve DM selfmanagement. We have designed the MAPPS-DM intervention to fill this gap.…”
Section: Introductionmentioning
confidence: 99%